Anisotropia unidirecional anômala induzida em bicamadas NiFe/IrMn - Krohling, Alisson Carlos (2015)
In this Master dissertation, anomalous unidirectional anisotropy and Exchange Bias effect on multilayer Si(100)/Ta(3nm)/NiFe(3nm)/IrMn(7nm)/Ta(1nm), prepared at room temperature by DC Sputtering, were systematically studied by X-ray difraction and magnetization measurements. In particular, as-prepared and heat at 600 K samples were investigated by X-ray diffraction in low (reflectivity) and high (conventional) angle geometries to characterize the bulk and interface film structural properties. Magnetization measurements, performed in a broad temperature range (300 - 600 K), were done to study magnetic properties of these two samples (as-prepared and annealed). Room temperature M(H) curves have shown a horizontal loop shift effect for the as-prepared sample. This effect was here associated with an anomalous unidirectional anisotropy induced during the sample preparation procedure (intrinsic properties), i. e., an effect that is present before the field cooling process needed to induce the Exchange bias effect. This anomalous behavior, observed in as-prepared Si(100)/Ta(3nm)/NiFe(3nm)/IrMn(7nm)/Ta(1nm) film, may be explained assuming an interface interduffusion effect without structural change at the Ta/NiFe interface. This interdiffusion effect, that occurs during the sample preparation, favors a magnetically harder NiFeTa phase (when compared with the NiFe phase); consequently there will be for the as-prepared film two magnetic contributions: (i) a soft NiFe phase magnetically coupled to the IrMn layer and that will be responsible for the observed horizontal loop shift effect (anomalous unidirectional anisotropy) and (ii) a harder NiFeTa phase, which is not influenced by the anomalous unidirectional anisotropy, but that have their magnetic moments rotated incoherently with those spins of the NiFe layer. The combination of low and high temperatures magnetic and structural data indicates that it is possible to remove this anomalous anisotropy when the sample is heated around the interval 520-570 K, which is the blocking temperature range of this effect. However, the high temperature data suggest an enhancement of the interface atomic interdiffusions Ta/NiFe and NiFe/IrMn, leading to a sample degradation as well as formation of a NiFeIrMnTa phase, with a completely disappearance of the NiFe contribution.